Sarcoma de Ewing pediátrico : papel da cintilografia óssea com sestamibi-99mTC associado ao grau de necrose - Bento Corrêa, Ana Paula, 1976- (2019)
Orientadores: Simone dos Santos Aguiar, Alejandro Enzo Cassone